Nematode Management for Golf Courses in Florida - William T. Crow (EDIS)
UF/IFAS is committed to providing the most current information on the notoriously difficult problem of managing nematodes on golf courses. This publication is updated and revised whenever there is a breaking development, to bring you the new information and management advice. This 8-page fact sheet was revised in January 2017 by William T. Crow and published by the UF Department of Entomology and Nematology.